2009
DOI: 10.1179/135100009x392485
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity of methanolic extract ofBombax ceiba

Abstract: This study aimed to examine the antioxidant activity of methanolic extract of various type of soybean (Glycine max L.Merill) i.e Argomulyo, Burangrang, Ijen, and Kaba by using DPPH (1,1-Diphenyl-2-picryhydrazyl) method. The soybean was crushed, defatted using n-hexan, and extracted using methanol 90%. The processes of defatting and extracting were conducted by kinesthetic maceration. Identification of flavonoid content using KLT and an assay of the antioxidant power of soybean were carried out qualitatively an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 28 publications
1
27
0
Order By: Relevance
“…Another molecules acetyl and cinnamoyl derivatives were found to be less active than mangiferin whereas, methyl and 3,6,7-trimethylether tetraacetate derivatives were inactive (Dar et al, 2005). Vieira et al (2009) also evaluated the antioxidant activity of methanolic extract of Bombax ceiba using (i) ability to scavenge DPPH and hydroxyl free radicals; (ii) action against lipid peroxidation and (iii) effect on myeloperoxidase activity. The extract showed significant antioxidant activity in all assays.…”
Section: Antioxidants Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Another molecules acetyl and cinnamoyl derivatives were found to be less active than mangiferin whereas, methyl and 3,6,7-trimethylether tetraacetate derivatives were inactive (Dar et al, 2005). Vieira et al (2009) also evaluated the antioxidant activity of methanolic extract of Bombax ceiba using (i) ability to scavenge DPPH and hydroxyl free radicals; (ii) action against lipid peroxidation and (iii) effect on myeloperoxidase activity. The extract showed significant antioxidant activity in all assays.…”
Section: Antioxidants Activitymentioning
confidence: 99%
“…The extract showed significant antioxidant activity in all assays. The extract showed very low toxicity toward Vero cells (Vieira et al, 2009). Methanolic extract of roots of Bombax ceiba was evaluated using DPPH radical scavenging assay and reducing power assay.…”
Section: Antioxidants Activitymentioning
confidence: 99%
“…In recent decades, the extracts of B ceiba have been extensively studied for many potential uses including moderate oxytocic activity and cardiac stimulant properties (Misra et al, 1968), hypotensive and hypoglycaemic activity (Saleem et al, 1999), analgesic and antioxidant activity (Dar et al, 2005;Vieira et al, 2009). An ethnobotanical study reported the use of B. ceiba as a traditional anti-inflammatory agent (Namsa et al, 2009).…”
Section: Original Articlementioning
confidence: 99%
“…Chand and Singh (1999) NCF Antioxidant (Vieira et al, 2009), hypoglycaemic (Saleem et al, 1999 (Shrestha et al, 2007), anti-inflammatory (Hajare et al, 2001) Ficus racemosa L. NCF Bhatta et al (2012) Hypercholesterolemia and diabetes protective (Velayutham et al, 2012), antidiarrheal (Mukherjee et al, 1998;Patil et al, 2012) Kundu et al (1983), Pinos-Rodriguez et al Antiulcerogenic (Megala and Geetha, 2012), (Roxb.) Benth.…”
Section: Resultsmentioning
confidence: 99%